Keamanan dan Privasi dalam Keuangan Digital - Siti Khoiriah; Annisa Salsabila; Daniel David Camberra; Erwan Syafri; Haqiqi Lina Layyin; Riangga Fathurrahman; Masno Marjohan (Pusat Riset dan Inovasi Nasional, 2025)
The rapid digitalization of the financial sector in Indonesia has significantly improved access to financial services but also raised serious concerns regarding the security and privacy of user data. Low levels of digital awareness among the public, coupled with uneven adoption of protective technologies such as encryption and blockchain, have intensified these vulnerabilities. This study aims to identify cybersecurity threats and risks in digital financial systems, evaluate the effectiveness of data protection technologies, and analyze the role of regulations and user education in strengthening data protection mechanisms. A systematic literature review was conducted using a qualitative descriptive approach, drawing on 20 national academic sources published between 2018 and 2025. The findings are grouped into four key themes: (1) technical and human-related security risks, (2) variation in the application of protective technologies, (3) institutional disparities in readiness for compliance with the 2022 Personal Data Protection Law, and (4) low privacy literacy among younger users. The study concludes that effective data protection requires synergy between regulation, technology, and digital literacy education. This research highlights the need for strict digital security audits and integrated privacy awareness campaigns within formal education and small business training programs.